2011
DOI: 10.1080/00288330.2011.587823
|View full text |Cite
|
Sign up to set email alerts
|

Influences of geology and land use on macroinvertebrate communities across the Motueka River catchment, New Zealand

Abstract: The influences of geology and land use on macroinvertebrate communities were investigated in the Motueka River catchment, New Zealand. Comparisons of functional feeding groups, multivariate community composition and biotic indices (MCI, QMCI, %EPT) were made between native forest stream reaches that differed in subcatchment geology (ultramafic, hard sedimentary, granite, gravel, karst) and between stream reaches surrounded by different land uses (native forest, exotic forest and pasture) within two of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Most of the MCI and QMCI scores for streams in mature planted forests gave a ranking of 'clean water' or, 'mild pollution' (Boothroyd and Stark 2000) (Table 2). A QMCI score indicative of 'probable moderate pollution' was recording in mature planted forest streams in the Moutere Gravels of the Nelson region (Shearer and Young 2011). This result was possibly influenced by an intermittent flow regime.…”
Section: Mature Forest Phase: Canopy Closure To Forest Maturitymentioning
confidence: 86%
See 3 more Smart Citations
“…Most of the MCI and QMCI scores for streams in mature planted forests gave a ranking of 'clean water' or, 'mild pollution' (Boothroyd and Stark 2000) (Table 2). A QMCI score indicative of 'probable moderate pollution' was recording in mature planted forest streams in the Moutere Gravels of the Nelson region (Shearer and Young 2011). This result was possibly influenced by an intermittent flow regime.…”
Section: Mature Forest Phase: Canopy Closure To Forest Maturitymentioning
confidence: 86%
“…A preliminary study by Fish (1968) found very low levels of Cu (often below detection (Collier and Bowman 2003;Cooper et al 1987;Fahey and Stansfield 2006;Friberg et al 1997;Harding and Winterbourn 1995;Macaskill et al 1997;Matheson et al 2011;Parkyn et al 2006;Thompson et al 2009;Thompson and Townsend 2004b;Townsend et al 1997;Young et al 2005). The wider range of NO 3 -N/ NO x -N concentrations compared with TN is influenced by studies that measured that measured concentrations of NO 3 -N at the high end of the range and either did not measure TN or measured TN at a lower sampling intensity than NO 3 -N. Death et al 2003;Friberg and Winterbourn 1997;Harding and Winterbourn 1995;Parkyn et al 2006;Quinn et al 1997;Quinn et al 2004;Shearer and Young 2011;Stark and Maxted 2007;Townsend et al 1997. 2 EPT: Ephemeroptera, Plecoptera, Trichoptera.…”
Section: Mature Forest Phase: Canopy Closure To Forest Maturitymentioning
confidence: 99%
See 2 more Smart Citations
“…The geological environment determines the basic geochemical composition of substrate, and erosion and sedimentation processes in rivers (Andrews and Antweiler, 2012;Dudgeon, 2012). Potentially, geology influences the magnitude that land use impacts on invertebrate communities (Shearer and Young, 2011). Geomorphology has a profound impact on physical variables of channel and flow type (Wei and Sun, 2009).…”
Section: Highlights Of the Methodsmentioning
confidence: 99%